Construction of MOF-derived hollow Ni–Zn–Co–S nanosword arrays as binder-free electrodes for asymmetric supercapacitors with high energy density. Issue 29 (16th July 2018) - Huang, Youzhang; Quan, Liang; Liu, Tianqing; Chen, Qidi; Cai, Daoping; Zhan, Hongbing
Abstract : Mesoporous and hollow Ni–Zn–Co–S nanosword arrays (NSAs) have been successfully grown on nickel foam (NF) through a simple two-step method, which would hold great promise for high-performance supercapacitors. Abstract : Mixed transition metal sulfides with hollow structures hold great promise for energy-related applications. However, most of them are in the powder form, which should be mixed with unwanted polymer binders and conductive agents. In this study, a facile two-step strategy has been developed to grow mesoporous and hollow Ni–Zn–Co–S nanosword arrays (NSAs) on a nickel foam (NF) substrate with robust adhesion, which involves the hydrothermal growth of bimetallic Zn–Co-ZIF NSAs on NF and subsequent transformation into hollow Ni–Zn–Co–S NSAs through the sulfurization process. Benefiting from the unique structural and compositional advantages as well as directly grown conductive substrate, the Ni–Zn–Co–S-0.33 NSAs/NF electrode exhibits the best electrochemical performance when investigated as a binder-free electrode for supercapacitors. Impressively, the Ni–Zn–Co–S-0.33 NSAs/NF electrode delivers a high areal capacity of 1.11 mA h cm −2 at the current density of 10 mA cm −2, and the corresponding specific capacity is as high as 358.1 mA h g −1 . Moreover, an asymmetric supercapacitor (ASC) device based on the Ni–Zn–Co–S-0.33 NSAs/NF as the positive electrode and Bi2 O3 /NF as the negative electrode has been successfully fabricated, and can deliver a high energy density of 91.7 W h kg −1 at a power density of 458 W kg −1 and maintain the energy density of 66.9 W h kg −1 at a high power density of 6696 W kg −1 . The electrochemical results suggest that the hollow Ni–Zn–Co–S NSAs would possess great potential for applications in high-performance supercapacitors.